Critical success factors in the TBL concept of sustainable entrepreneurship. (2016) - Tarnanidis, Theodore; Papathanasiou, Jason; Subeniotis, Demetres
This research presents a generalised measurement model of sustainable entrepreneurship goals. It re-examines the approach for capturing and incorporating the triple bottom line concept (TBL) of economic, ecological and social goals. The literature overview has shown that research in the area of sustainable entrepreneurship is still growing, as there is a lack of research that sheds light on the elaboration of an aggregate measure. In doing so, we collected data from 150 Greek food companies by applying the method of structural equation modelling from different stakeholders. To that extent we utilised the fundamental scale development recommendations. We developed a parsimonious inventory of 12-itemed with four factors. The evolving contextualisation could serve as an initial starting point for venture capitalists to craft better entrepreneurial plans and managerial strategies.